Defects of communication pipes from plastic in modern civil engineering - Lyashenko, V.; Ahmad, M. Ayaz; Sotnik, S.; Deineko, Z.; Khan, Alveera (TJPRC Pvt. Ltd., 2018)
Plastic is an important material that is used in civil engineering. Communication pipes - one of the directions of use of plastic. The external environment affects the quality of the use of plastic pipes. Therefore it is important to know the defects of plastic products. It is also necessary to make assessment of the quality of the use of plastic pipes. It depends on many factors. Therefore the task of detection and preventing of the communication pipes defects - the complex task. We did a survey of the major defects of the communication pipe. We have examined the factors that influence the formation of defects in the communication pipe. A classification of variable factors that affect the quality of communication pipes is proposed. A generalized algorithm for evaluating the quality of communication pipes has also been developed.
Keywords: Defects; Plastic